Encyclopedias about Muslim civilisations - Khanbaghi, Aptin (Muslim civilisation abstracts, 2009)
This is an innovative reference catalogue of 200 annotated bibliographies and abstracts of encyclopaedias published during the nineteenth, twentieth and twenty-first centuries. Material is presented in English, Arabic and Turkish